Modern Gnostics: The Pursuit of the Sacred in Indonesian Islam - Kahn, Joel S. (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
This  paper  reports  on  an  ongoing  research  project  on  “New  Southeast Asian  Spiritualties”  and  offers  a  preliminary  analysis  of  new  Muslim religiosities in the Jakarta metropolitan area (Jabodetabek). Most of the analyses of the processes of “Islamization” in places like Indonesia and Malaysia in the last few decades focus on a particular set of social cum political  agendas:  the  imposition  of  sharia  law,  the  Islamization  of  the state  apparatus,  the  increased  emphasis  on  the  external  markers  of ‘Islamic  identity’  and  the  like.  Yet,  there  appears  to  be  an  equally significant,  even  sometimes  opposing,  tendency  among  Southeast  Asian Muslims that involves them in seeking out more intense and personalised ‘inner’ forms of religious experience, a process with parallels elsewhere in the world. In the paper, I discuss examples of this tendency based on fieldwork in the greater Jakarta area, and ask about its implications for current understandings of the consequences (for democracy, secularism, human rights, gender relations, etc.) of Islamization in Southeast Asia.